Best Answer

Since the second equation is already solved for "y", you can replace "y" by "9" in the other equation. Then solve the new equation for "x".

Q: Solve using substitution x plus y equals 3 and y equals 9?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

You'd need another equation to sub in

-2

Solve this system of equation using substitution 2x plus 6y equals 24 and 3x-2x equals 24 ?Improved Answer:2x+6y = 243x-2x = 24 => x =24Substitute the value of x into the top equation to find the value of y:48+6y = 246y = 24-486y = -24y = -4So: x = 24 and y = -4

This is not Calculus.y=7(Already solved)substiute y=7 into y=8xtherefore 7 = 8xtherefore x = 7/8

From second equation: y = 8 + 2xSubstitute for y in first equation: 3x + 16 + 4x = 2ie 7x = -14ie x = -2 and y = 4

Related questions

You'd need another equation to sub in

-2

Solve this system of equation using substitution 2x plus 6y equals 24 and 3x-2x equals 24 ?Improved Answer:2x+6y = 243x-2x = 24 => x =24Substitute the value of x into the top equation to find the value of y:48+6y = 246y = 24-486y = -24y = -4So: x = 24 and y = -4

This is not Calculus.y=7(Already solved)substiute y=7 into y=8xtherefore 7 = 8xtherefore x = 7/8

(2,3)

x = -2 and y = 1

From second equation: y = 8 + 2xSubstitute for y in first equation: 3x + 16 + 4x = 2ie 7x = -14ie x = -2 and y = 4

From first equation: y = 5 - 5xSubstitute for y in second equation: 3x + 10 - 10x = 3ie -7x = -7ie x = 1 and y = 0

If: x+y = 4 and y = 2x+1 Then: 4-x = 2x+1 => 3 = 3x => 1 = x So by substitution: x = 1 and y = 3

It is not possible to do so because the question contains one equation (5x + y = 1) and one expression (3x + 2y + 2). An expression cannot be solved.

When using substitution the answer to y0.5x plus 2 -y-2x plus 4 is y = -2 (x-1.

x=6y-4x=-2y+28Substitute (6y-4) for x in the second equation and solve for y:6y-4=-2y+288y=32y=4Then solve for x:x=6(4)-4=20(20,4)